Ultra low power wide-band mixer circuit based on subthreshold operation for MB-OFDM UWB. (April 2016) - Ragheb, A.N.; Kim, HyungWon
Abstract: This paper presents an extremely low power down-conversion mixer based on subthreshold operation for MB-OFDM UWB receiver, for the first band of operation 3.1–3.628 GHz. The proposed down-conversion mixer uses a double balanced Gilbert cell to provide the required performance in the conversion gain (CG) and the isolation among ports. It includes an input matching network (IMN) to enhance the input matching of the mixer. The proposed mixer is designed such that all transistors work in subthreshold regime under a supply voltage of 0.5 V, thus resulting in extremely low power consumption. We implemented the proposed mixer using a 0.18 μ m CMOS process. Simulation experiments show that the conversion gain of the mixer is 2.17–3.25 dB over the frequency range of 3.1–3.628 GHz when IF port is terminated with 50  Ω . The noise figure of the mixer is 5.12–5.93 dB, while the LO-IF isolation is lower than −111 dB. The 1-dB compression point is −16.68 dBm, third-order input intercept point IIP3 is −5.7 dBm. The experiments show that the proposed design consumes only 6.6 uW at 0.5 V, which is extremely low power compared with existing work.